Instagram as a pedagogical tool in pediatric dentistry and ortodontic courses = Instagram como herramienta pedagógica en cursos de odontopediatría y ortodoncia - Gutiérrez Marín, Natalia 1975-; Miranda Garro, Ingrid 1977-; López Soto, Andrea María 1987- (2024)
Social networks have become an ideal space for the exchange of information and knowledge. The objetive of this study was to determine the usefulness of the implementation of Instagram as a didactic tool to promote and facilitate student learning in the theoretical and laboratory courses of Pediatric Dentistry and Orthodontics during 2022. Private Instagram accounts were created for each of the four courses. During 4 months relevant information was posted to review concepts and strengthen the teaching-learning process of the students. At the end of the courses, a survey was conducted containing the following variables: usefulness of the social network, amount of information provided, preferred place to view content (wall or stories) and whether students recommend the use of Instagram in other courses of the Department of Dentistry and Orthodontics. For the association of variables, the chi-square test was used, value of p<0.05, 95%Cl. The participation in the accounts was 222 individuals; the interaction of the students with the accounts was 87.5% with respect to the stories, 95% observed the stories completely. There was a statistically significant difference with respect to where the information was posted: stories was the preferred place for students. There were 167 students participating in the survey. All the students found very useful or useful the content of the application on the social network.100% of the respondents recommended keeping the implementation of social networks in the theoretical courses of the Department. Instagram is not only a social application but also a channel to make the teaching process more dynamic and attractive. Teachers can integrate this social platform to foster motivation and learning in students.
Las redes sociales se han convertido en un espacio idóneo para el intercambio de información y conocimiento. El objetivo de este estudio fue determinar la utilidad de la implementación de Instagram como herramienta didáctica, para fomentar y facilitar el aprendizaje del estudiantado en los cursos teóricos y de laboratorio de Odontopediatría y Ortodoncia durante el 2022. Se crearon cuentas privadas en Instagram para cada uno de los cuatro cursos. Durante 4 meses se posteó información de relevancia para repasar conceptos y fortalecer el proceso de enseñanza- aprendizaje de los estudiantes. Al finalizar los cursos se realizó una encuesta que contenía las siguientes variables: utilidad de la red social, cantidad de información proporcionada, lugar preferido para ver el contenido (muro o historias) y si los estudiantes recomiendan el uso de Instagram en otros cursos del Departamento de Odontopediatría y Ortodoncia. Para la asociación de variables se utilizó la prueba de chi-cuadrado, el valor de p<0,05, 95%Cl. La participación en las cuentas fue de 222 individuos; la interacción de los estudiantes con las cuentas fue del 87,5% respecto a las historias, el 95% observaron las historias de forma completa. Hubo una diferencia estadísticamente significativa respecto al lugar donde se publicaba la información: las historias fue el lugar preferido por los estudiantes. La participación en la encuesta fue de 167 estudiantes. A todos los estudiantes les resultó muy útil o útil el contenido en la red social. El 100% de los encuestados recomendaron mantener la implementación de las redes sociales en los cursos teóricos del Departamento. Instagram no es solo una aplicación de carácter social, sino que constituye un canal para hacer el proceso de enseñanza más dinámico y atractivo. Los docentes pueden integrar esta plataforma social para fomentar la motivación y el aprendizaje en los en los estudiantes.
En revista Odóvtos, vol. 26, no.2 (mayo-agosto 2024)
Descripción basada en el contenido visto el 03 de febrero, 2025
También disponible en formato HTML y EPUB